Microbiome analysis reveals soil microbial community alteration with the effect of animal excretion contamination and altitude in Tibetan Plateau of China - Aoyun Li; Yaping Wang; Yajing Wang; Hailong Dong; Qingxia Wu; Khalid Mehmood; Zhenyu Chang; Ying Li; Yung-Fu Chang; Lijun Shi; Zhaoxin Tang; Hui Zhang (International Soil and Water Conservation Research, 2021)
The fertile forages in the Tibetan Plateau provide natural conditions for animal husbandry, whereas it is still unclear that whether animal excretion can result in the alteration of soil microbial community. Therefore, this study was performed to investigate the impact of animal excretion contamination and land altitude on the soil microbial community in different grazing areas of Tibetan Plateau. A total of 1160,190 high-quality valid sequences and 25,478 operational taxonomic units were achieved from 18 samples at three different altitude sites (Linzhi, Rikaze and Shannan). Here, we found excremental contamination did not alter the richness and diversity of soil microbial community, but it resulted in a significant alteration in the proportion of some bacteria. Specifically, the proportion of Proteobacteria in the LZa was obviously increased, whereas Gemmatimonadetes was significantly decreased as compared to LZe. Moreover, significant difference can also be observed in Verrucomicrobia between RKZe and RKZa. Remarkably, we also found that excremental contamination significantly decreased the abundance of some bacterial genera, such as Sphingopyxis, Polycyclovorans, Singulisphaera Cohnella, Polycyclovorans, Defluviicoccus, and Arthrobacter, which were closely related to soil health, pollutant degradation, and nutrient metabolism. Importantly, excremental contamination increased the proportion of harmful and beneficial bacteria in soil, such as the percentage of Acidibacter, Gemmatimonadaceae and Pajaroellobacter increased, while the ratio of Pontibacter, Flavisolibacter, Parasegetibacter, and Niastella decreased. Remarkably, soil samples collected from different altitude sites also displayed different soil microbial community structures. Our results demonstrated that excremental contamination could alter the soil microbial community structure and affect the normal function of the soil by affecting the proportion of harmful bacteria to beneficial bacteria. Moreover, this study can also provide a theoretical basis for the establishment of a supervision system for soil quality in Tibet.